До походження гривні - Козубовський, Г.А. (Археологія і давня історія України, 2021)
У статті розглядається проблема походження слов’янської гривні. Звертається увага на стародавні та середньовічні зернові та земельні міри Ірану, Кавказу та інших країн Передньої Азії. Їх
аналіз дозволяє припускати, що першопочатки слов’янської гривні походять від східної хлібної міри
«gryw» («grîw», вірм. «gryv») чи їх похідних. І зернова
міра передувала усім іншим: мірі ваги, грошового знаку, прикрасі. The article is devoted to the problems of the Old
Slavonic grivna. The word is present in all Slavonic
languages and associates with decoration, weight and
monetary unit. Many researchers link word a grivna as
derived from animal mane. Study of the Persian, Caucasian
and some other East writings and archeological
sources of the 1st millennium BC to the 1st millennium
AD (T. Nöldeke, H. Hübscmann, J. Harmatta, A. Manandyan,
W. Hinz, A. Bivar, H. Martirosyan and other)
has allowed to select many variant off this word, how
corn measure and land measure. This measure is fixed
in Old Persian, Middle Persian, Armenian, Georgian,
Parthian, Arabic and other languages (grb, grbn, grϊβa,
griv, grїw, garib, jarib and other). Grb (graβi, basket)
is present in Aramaic-Egyptian document and is dated
near 310 BC. How corn measure, the word was widespread
in the Achemenid and Sasanian Empire. Attested
as Armenian corn measure in the Anania Sirakaci,
7th century (9.782 kg, 1.5 modius, a unit of measurement),
links with garw-o-y, barley. However, in Greek
version inscription of Šāpur I (240—271), the word can
be correspond to 9.32 litres (A. Bivar). Griv as corn
measure is fixed on Caucasus in the end of the 1st millennium
— beginning of 2st millennium AD. Special attention
is spared to geographical terminology, in East
Europe word griva are spread for mountain territory and
area of land. Obviously, griv-modius how a corn measure
preceded to grivna-decoration, to grivna-weight and
to grivna-monetary unit in the Slavonic territories. The
Eastern Europe in the end of 1st millennium BC and the
1st millennium AD was a territory of agrarian economy,
and corn measure defined all others: capacity, length
and square, weight measures and monetary units.